(untitled) (University Journal of Zoology, Rajshahi University, 2013)
This study was conducted in Rajshahi and Natore districts of northern area of Bangladesh for a period of three years (2007 to 2009). One hundred carp ponds were selected randomly and fish farmers were interviewed to reveal the existing constraints and prospects. Ten percent farmers reported multiple ownership as a problem and 16% farmers stated that lease value of pond is too high which reducing their profit level. Lack of quality fish seeds was reported by 33% farmers which results in low growth and high mortality of fishes. Nine percent carp farmers reported that inorganic fertilizers were not giving expected performances. Thirty three percent carp farmers failed to apply required inputs in due time due to lack of sufficient credit. Plankton bloom was recorded in 18% ponds. Three percent fish farmers were found to be affected by flood and drought. Eight percent farmers reported non-severe attack of disease. Fish poaching and poisoning were revealed as major constraints. Thirty six percent farmers mentioned lack of technical supports. Due to found constraints, the farmers failed to use inputs and experiences properly resulted in unsatisfactory fish production (3598.72±785.83 kg/ha/yr) to the carp farmers. Further research efforts are recommended to assess the specific impacts of recorded constraints on fish production. DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15435 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 69-72